Conjunctival cytology in floppy eyelid syndrome: objective assessment of the outcome of surgery. Issue 4 (5th December 2008) - Medel, R; Alonso, T; Vela, J I; Calatayud, M; Bisbe, L; García-Arumí, J
Abstract : Aims: Upper eyelid shortening is the main surgical procedure in floppy eyelid syndrome (FES). The efficacy of surgery is assessed by improvements in the symptoms, since objective evaluation is difficult. Conjunctival impression cytology was assessed as an objective method for the evaluation of the effectiveness of surgery for FES. Method: The study was a prospective interventional study in 16 patients (26 eyelids) with FES, who were enrolled over a period of 8 months. Patients were examined 1–4 weeks before surgery and 16 weeks after surgery. Cases were classified into three groups according to the severity of symptoms and papillary reaction. A full-thickness pentagonal wedge resection was performed in the upper eyelid. Impression cytology was performed in all patients at 1–4 weeks before surgery and 16 weeks after surgery. Results: Postoperative improvements in cellular morphology and goblet cell count were found in 20 of 22 eyelids (91%) and this led to a decrease of least one grade in Nelson's classification. In two cases (9%) the Nelson grade remained stable. Postoperative improvement on cytology was statistically significant with the Wilcoxon signed ranks test (p<0.001). Conclusion: Conjunctival cytology provides an objective method for the evaluation of the efficacy of surgical techniques proposed for the treatment of eyelid laxity syndromes.